ANALISIS TINGKAT KOGNITIF SOAL UJIAN SEKOLAH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM BERDASARKAN TAKSONOMI BLOOM REVISI 2001 - Annisa Siti Nurhaliza; Mochamad Fiqri Mustopa (IAIN Pontianak, 2023)
This study aims to analyze the cognitive level of school exam questions on Islamic Religious Education subjects based on Bloom's Revised Taxonomy. Bloom's Revised Taxonomy is used as an assessment framework to describe the level of cognitive complexity requested by each exam question. The research method used was content analysis of Islamic Religious Education question banks from several schools covering primary and secondary education levels. The results of the analysis show that most of the Islamic Religious Education exam questions still concentrate on lower cognitive levels such as remembering and understanding. Higher cognitive levels such as applying, analyzing, evaluating and creating are rarely found in these questions. This indicates a tendency to use questions that tend to ask students to remember and understand religious concepts, rather than encouraging critical and analytical thinking skills